A comparative evaluation of chewing efficiency, masticatory bite force, and patient satisfaction between conventional denture and implant-supported mandibular overdenture: An in vivo study - Arjun Jawahar Sharma; Rahul Nagrath; Manesh Lahori (Wolters Kluwer Medknow Publications, 2017)
Purpose: The purpose of this within-subject crossover clinical trial was to compare and evaluate the chewing efficiency, masticatory bite force, and patient satisfaction with conventional dentures and two implant-retained mandible overdentures after 4 weeks of usage. Method: This within-subject crossover clinical trial was carried out in the Department of Prosthodontics in K.D Dental College and Hospital. A total 15 patients were selected for the study. To report the changes in chewing efficiency by chewing 6gms of peanuts with 40 chewing strokes and comparing the particle size of the chewed material between two implant retained mandibular overdenture with that of conventional denture using micro vu excel gantry type visual measurement machine. To report changes in masticatory bite force after transition of conventional complete denture patient to implant retained overdenture after using the prosthesis for four weeks each and recorded by digital transducer. To assess the patient satisfaction after transition of conventional complete denture patient to implant retained mandibular overdenture with help of OHIP edent patient satisfaction questionnaire. Results: The chewing efficiency for implant retained overdenture increased significantly than that of conventional denture. The particle size decreased to 76.34% for implant supported overdenture than that of conventional denture. The chewing strokes required by conventional denture was 69 strokes and that by implant supported overdenture which was 40 strokes to get the same mean particle size. The patients satisfaction after receiving the implant retained overdenture was significantly higher than that of complete denture. Conclusion: The provision of two mandibular implants significantly improves measures of oral function and better quality of life for edentulous patients.